2016
DOI: 10.1186/s40168-016-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness as a predictor of intestinal microbial diversity and distinct metagenomic functions

Abstract: BackgroundReduced microbial diversity in human intestines has been implicated in various conditions such as diabetes, colorectal cancer, and inflammatory bowel disease. The role of physical fitness in the context of human intestinal microbiota is currently not known. We used high-throughput sequencing to analyze fecal microbiota of 39 healthy participants with similar age, BMI, and diets but with varying cardiorespiratory fitness levels. Fecal short-chain fatty acids were analyzed using gas chromatography.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
331
6
18

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(390 citation statements)
references
References 53 publications
35
331
6
18
Order By: Relevance
“…Independently of their diet, the higher the fitness level, the more diverse was their gut microbiome. Increased pruduction of butyrate, as a marker of gut health, and increased abundance of butyrate-producing taxa were also A C C E P T E D M A N U S C R I P T measured in individuals with greater levels of aerobic fitness [98]. Regardless of age, carbohydrate-or fat intake, Yang et al confirmed the association between cardiorespiratory fitness and gut microbiota composition in 71 premenopausal women [99].…”
Section: After Normalizing Bmi Diet Age Estaki Et Al Analyzed Fecsupporting
confidence: 58%
See 1 more Smart Citation
“…Independently of their diet, the higher the fitness level, the more diverse was their gut microbiome. Increased pruduction of butyrate, as a marker of gut health, and increased abundance of butyrate-producing taxa were also A C C E P T E D M A N U S C R I P T measured in individuals with greater levels of aerobic fitness [98]. Regardless of age, carbohydrate-or fat intake, Yang et al confirmed the association between cardiorespiratory fitness and gut microbiota composition in 71 premenopausal women [99].…”
Section: After Normalizing Bmi Diet Age Estaki Et Al Analyzed Fecsupporting
confidence: 58%
“…SCFAs in 39 healthy subjects (male and female) with different levels of cardiorespiratory fitness [98]. Independently of their diet, the higher the fitness level, the more diverse was their gut microbiome.…”
Section: After Normalizing Bmi Diet Age Estaki Et Al Analyzed Fecmentioning
confidence: 99%
“…Supporting previous insights into the beneficial influence of physical exercise and associated diet on the compositional structure of the gut microbiota,25 26 30 this study has extended the paradigm to include links between physical fitness and the functional potential of the gut microbiota and its metabolites. It must be conceded that some athletes, although fit, may not necessarily be more healthy 31…”
Section: Discussionmentioning
confidence: 68%
“…The gut microbiota is perturbed by antibiotic usage and is influenced by short-term and long-term dietary trends. Recently, the interaction between exercise and the gut microbiota has been highlighted following identification of correlations between cardiorespiratory fitness and health-associated gut microbial parameters such as taxonomic diversity and richness 5 6. It is unknown whether improvements in cardiorespiratory fitness achieved during adulthood can shift the gut microbiota towards a more healthy compositional profile.…”
Section: Exercising Your Microbiotamentioning
confidence: 99%